2018
DOI: 10.1038/s41419-018-1110-z
|View full text |Cite
|
Sign up to set email alerts
|

Increasing G9a automethylation sensitizes B acute lymphoblastic leukemia cells to glucocorticoid-induced death

Abstract: Synthetic glucocorticoids (GCs) are used to treat lymphoid cancers, but many patients develop resistance to treatment, especially to GC. By identifying genes that influence sensitivity to GC-induced cell death, we found that histone methyltransferases G9a and G9a-like protein (GLP), two glucocorticoid receptor (GR) coactivators, are required for GC-induced cell death in acute lymphoblastic leukemia (B-ALL) cell line Nalm6. We previously established in a few selected genes that automethylated G9a and GLP recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…Such methylation is required for forming complex with heterochromatin protein 1γ (HP1γ) to regulate gene expression. Importantly, increased G9a methylation enhances the G9a binding to HP1γ, sensitizing acute lymphoblastic leukemia (B‐ALL) cell line resistant to synthetic glucocorticoids treatment 72 . Another typical example is the epigenetic silencing complex polycomb repressive complex 2 (PRC2) which is solely responsible for the trimethylation of histone H3K27.…”
Section: Targeting Ptm Protein Isoforms In Drug Designmentioning
confidence: 99%
“…Such methylation is required for forming complex with heterochromatin protein 1γ (HP1γ) to regulate gene expression. Importantly, increased G9a methylation enhances the G9a binding to HP1γ, sensitizing acute lymphoblastic leukemia (B‐ALL) cell line resistant to synthetic glucocorticoids treatment 72 . Another typical example is the epigenetic silencing complex polycomb repressive complex 2 (PRC2) which is solely responsible for the trimethylation of histone H3K27.…”
Section: Targeting Ptm Protein Isoforms In Drug Designmentioning
confidence: 99%
“…[ 32 ] Moreover, it has been reported that overexpression of G9a causes cell proliferation and metastasis in several human cancers, such as breast, [ 18 ] ovarian, [ 33 ] head and neck, [ 34 ] gastric, [ 22 ] colon, [ 15 ] lung, [ 17 ] bladder, [ 23 ] liver, [ 19 ] cervical, [ 16 ] prostate, [ 35 ] neuroendocrine tumors, [ 36 ] and hematological malignancies. [ 21 ] G9a‐mediated H3K9 di‐methylation silences the antioncogene genes, resulting in a potential increase in cancer cell proliferation. [ 2 ] Furthermore, G9a and GLP di‐methylate to the lysine 373 residue of tumor suppressor gene p53, lead to transcriptional inactivation of p53 and increase cancer cell proliferation.…”
Section: G9a Histone Methyltransferasementioning
confidence: 99%
“…[ 2 ] G9a overexpression was observed in malignancies, including lung, colon, gastric, breast, bladder, skin, gastric, cervical cancers, hepatocellular carcinoma, and hematological malignancies. [ 14–23 ] In this review, we discussed the involvement of G9a‐ and GLP‐mediated epigenetic regulation in the pathogenesis of cancer and how their targeting by G9a and GLP inhibitors could be a possible therapeutic approach for cancers treatment and management.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of G9a and GLP inhibitors developed to date include, but are certainly not limited to, BIX-01294 (Kubicek et al, 2007), UNC0638 (Vedadi et al, 2011), UNC0642 (Liu et al, 2013), A-366 (Sweis et al, 2014), and CSV0C018875 (Charles et al, 2020). Modulation of G9a function with chemical inhibitors has presented to be beneficial for sensitization to other standard chemotherapeutics, as described regarding enhancing G9a auto-methylation in combination with glucocorticoid treatment (Poulard et al, 2018). This is the case for direct inhibitors of G9a and GLP methyltransferase activity.…”
Section: Hypoxic Methylation and Pathological Relevancementioning
confidence: 99%
“…Clearly, modulating G9a expression and activity has potential as a therapeutic strategy. Further, increased self/auto-methylation of G9a has been found to restore the sensitivity of glucocorticoid-resistant acute lymphoblastic leukemia tumors to glucocorticoid treatment ( Poulard et al, 2018 ). Examples of G9a and GLP inhibitors developed to date include, but are certainly not limited to, BIX-01294 ( Kubicek et al, 2007 ), UNC0638 ( Vedadi et al, 2011 ), UNC0642 ( Liu et al, 2013 ), A-366 ( Sweis et al, 2014 ), and CSV0C018875 ( Charles et al, 2020 ).…”
Section: Hypoxic Methylation and Pathological Relevancementioning
confidence: 99%